Panel data analysis of internal conflict and income inequality - Brandon Parsons; Shahdad Naghshpour (European Journal of Government and Economics (EJGE), 2023)
The study determines how worsening internal and external conflict affects income inequality. The paper accounts for contributing variables and analyzes panel data in an unbalanced panel of 106 countries from 1988 to 2018-the panel data model groups by development status. The econometric model uses Driscoll and Kraay standard errors to account for heteroscedasticity, cross-sectional dependence, and autocorrelation. Worsening internal conflict increases income inequality in developing countries but not in developed countries. Worsening of internal conflict by one standard deviation increases income inequality by 0.068 in developing counties. External conflict does not noticeably affect income inequality in developed or developing panels.
Keywords: 330; income inequality; Gini coefficient; internal conflict; external conflict